Peningkatan PENINGKATAN PRODUKSI USAHA TERASI AWAINA DI KOTA LANGSA MENGGUNAKAN TEKNOLOGI SCREW PRESS MACHINE SEBAGAI PENCETAK TERASI - Fajriani Fajriani; Haikal Fajri; Nirmala Sari; Sabrian Tri Anda; T. Andi Fadly; Ida Ratna Nila (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
One of the household businesses in the field of shrimp paste processing located in Gampong Simpang Lhee, West Langsa District, Langsa City is terasi awaina. From the observations that have been made, the process of printing shrimp paste is still carried out conventionally using hands, so the process of printing shrimp paste takes a long time and produces a paste print that is not uniform in size, therefore the PKM team offers an appropriate technology in the form of a screw press machine as a paste printer. The method of this community service activity is carried out by providingn information and solutions about the products offered, as well asstrengthening the screw press machine design needed by partners, then conducting training on how to operate and maintain the screw press machine , then the latter performs mentoring during and after the program. From the results of the evaluation that has been carried out by the PKM team, it is certain that the business of terasi awaina gampong simpang lhee has been skilled in using screw press machines, it is hoped that with the screw press machine, the production of awaina paste will increase.